2022
DOI: 10.3390/brainsci12020193
|View full text |Cite
|
Sign up to set email alerts
|

Neurological Prognostic Factors in Hospitalized Patients with COVID-19

Abstract: We aimed to search whether neurological symptoms or signs (NSS) and the MEWS (Modified Early Warning Score) score were associated with in-hospital mortality or oxygen requirement during the first 14 days of hospitalization in COVID-19 patients recruited at the University Hospital in Krakow, Poland. The detailed clinical questionnaires on twenty NSS were either filled out by patients prospectively or retrospectively assessed by neurologists based on daily medical records. NSS were considered high or low-risk if… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 58 publications
1
8
0
3
Order By: Relevance
“…Therefore, it seems that female sex is the only consistent risk factor for residual post-COVID fatigue, both in younger [40] and older populations [41]. Notably, our cohort consisted mainly of patients in a relatively good clinical condition prior to the SARS-CoV-2 infection, as the prevalence of diseases known to increase COVID-associated mortality, such as stroke, dementia and neoplasm, was below 10% [3,[42][43][44].…”
Section: Discussionmentioning
confidence: 97%
“…Therefore, it seems that female sex is the only consistent risk factor for residual post-COVID fatigue, both in younger [40] and older populations [41]. Notably, our cohort consisted mainly of patients in a relatively good clinical condition prior to the SARS-CoV-2 infection, as the prevalence of diseases known to increase COVID-associated mortality, such as stroke, dementia and neoplasm, was below 10% [3,[42][43][44].…”
Section: Discussionmentioning
confidence: 97%
“…Five studies (Husain, Talavera, Porta-essem, Rocha-Filho, and Drabik) in our review stated that patients with anosmia and/or ageusia are correlated with lower mortality. (5,8,17,18) The study performed by Rocha-Filho also showed that anosmia and ageusia correlated with a shorter length of stay in the hospital (17). While a study performed by Husain showed that anosmia is correlated with a milder disease trajectory (5).…”
Section: Anosmia and Ageusia As A Diagnosis And Prognostic Factorsmentioning
confidence: 96%
“…Drabik и соавт. [8] провели когортное исследование с целью выяснить, связаны ли неврологические симптомы и оценка по шкале MEWS (Modified Early Warning Score, мо-ВВЕДЕНИЕ В марте 2020 г. Всемирная организация здравоохранения объявила заболевание COVID-19, вызванное коронавирусом SARS-CoV-2, глобальной пандемией, и с тех пор во всем мире зарегистрированы 578 142 444 случая заболевания и 6 405 080 смертельных исходов (по состоянию на 04.08.2022) [1]. Коронавирус SARS-CoV-2 -одноцепочечный РНК-вирус из семейства Coronaviridae с двухслойной фосфолипидной капсулой, содержащей шиповидный S(spike)-белок.…”
Section: острые нарушения мозгового кровообращенияunclassified